Implementing a reconfigurable Internet of Things Nodes using non-IP network based on Wireless Sensor Network - Khalida S. Rijab; Saif Muqdad Sadiq (Diyala Journal of Engineering Sciences, 2019)
The idea of using wireless sensor network (WSN) let’s as to upload multiple node’s data over one IP, to reduce the number of needed IP multiple nodes, it’s necessary  to provide a backup sink for the data to let the sensors send their data via the link B when the link A is down. Therefore a web-portal has been designed with a debug terminal for the proposed IoT system to let us reconfigure the nodes and change the path of the wireless sensor network data. Two sink-nodes has been implemented for the proposed system, first one (A) for major data path that collected the data from sensors and uploads it to the web-portal and the second one (B) acts as a backup link for the data path. In the proposed system, we used the esp33 as a Wi-Fi connection for the wireless sensor network, and the NRF24 wireless transceiver module used to send the data from nodes to esp32